Pengaruh Kompetensi Pedagogik Guru, Disiplin Belajar, Bimbingan Orang Tua dan Motivasi Belajar Terhadap Hasil Belajar Kejuruan Akomodasi Perhotelan Kelas XII Perhotelan di SMK Duta Bangsa Denpasar - N.M Antariani; D.G.H Divayana; I.P.W. Ariawan (Pascasarjana Universitas Pendidikan Ganesha, 2021)
This study aims to describe the magnitude of the influence of several variables, namely: (1) teacher pedagogic competence, (2) learning discipline, (3) parental guidance, and (4) learning motivation on learning outcomes of vocational students of class XII Hospitality at SMK Duta Bangsa Denpasar. The population in this study were students of class XII Hospitality, amounting to 44 people. This research was designed ex-post-facto. Data were collected by questionnaire. Data analysis was performed using simple regression technique, multiple regression and partial correlation. The results showed that: (1) there was a significant influence of teacher pedagogic competence on the results of vocational learning accommodation accommodation class XII at SMK Duta Bangsa Denpasar with a coefficient of determination of 29.4% and an effective contribution of 3%, (2) there was a significant influence of discipline learning on vocational learning outcomes for hotel accommodation class XII hospitality at SMK Duta Bangsa with a coefficient of determination of 77% and an effective contribution of 68%, (3) there is a significant influence of parental guidance on vocational learning outcomes for class XII hospitality accommodation at SMK Duta Bangsa Denpasar with a coefficient of determination of 55.6% and an effective contribution of 5%, (4) there is a significant influence of learning motivation on vocational learning outcomes for hotel accommodation class XII hospitality at SMK Duta Bangsa Denpasar with a coefficient of determination of 6.2% and an effective contribution of 2 %, (5) together, there is a significant influence g significant pedagogic competence, learning discipline, parental guidance and learning motivation on the vocational learning outcomes of hotel accommodation class